Check GMAT Club Decision Tracker for the Latest School Decision Releases https://gmatclub.com/AppTrack

 It is currently 27 May 2017, 23:14

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# Is |S-R|>|T-U|? (1)|R-T|>|S-U| (2)|R-U|>|S-T|

 post reply Question banks Downloads My Bookmarks Reviews Important topics
Author Message
CEO
Joined: 15 Aug 2003
Posts: 3454
Followers: 67

Kudos [?]: 874 [0], given: 781

Is |S-R|>|T-U|? (1)|R-T|>|S-U| (2)|R-U|>|S-T|  [#permalink]

### Show Tags

07 Dec 2003, 18:31
00:00

Difficulty:

(N/A)

Question Stats:

0% (00:00) correct 0% (00:00) wrong based on 0 sessions

### HideShow timer Statistics

This topic is locked. If you want to discuss this question please re-post it in the respective forum.

Is |S-R|>|T-U|?

(1)|R-T|>|S-U|
(2)|R-U|>|S-T|

Make an effort to explain. It helps the new guys and me too!

thanks
praetorian
Intern
Joined: 20 Oct 2003
Posts: 13
Location: Moscow
Followers: 0

Kudos [?]: 0 [0], given: 0

### Show Tags

08 Dec 2003, 07:43
May be I am wrong, but there should be one who tried it to provide a basis for discussion:

[S-R] > [T-U]
opening the inequality gives:
A. S-R > T-U
B. S-R < U-T

solving gives
S>R

same logic applied for 1 & 2:

1. S<U , INSUFFICIENT
2. S<T, INSUFFICIENT

Intern
Joined: 04 Oct 2003
Posts: 42
Location: Silicon Valley, CA
Followers: 0

Kudos [?]: 1 [0], given: 0

### Show Tags

09 Dec 2003, 02:05
|S-R|>|T-U|?

(1)|R-T|>|S-U|
(2)|R-U|>|S-T|

Stem says
S-R > T-U or S-R<U-T
=> S+U> T+R or S+T<U+R

1) R+U>S+T or R-T<U-S => R+S<U+T ; insufficient

2) R-U>S-T or R-U<T-S
R+T>S+U or R+S<T+U; insufficient

together we can get both the conditions of the stem. Hence Ans=3, that is both taken together are sufficient.
SVP
Joined: 30 Oct 2003
Posts: 1790
Location: NewJersey USA
Followers: 6

Kudos [?]: 101 [0], given: 0

### Show Tags

13 Dec 2003, 18:53
I am sorry to say that the following logic is wrong.
[S-R] > [T-U]
opening the inequality gives:
A. S-R > T-U
B. S-R < U-T

for example take s = -16, r = -10, t = -15, u = -10
|s-r| = | -16+10 | = |-6| = 6
|t-u| = | -15+10 | = |-5| = 5
this satisfies the condition |s-r| > |t-u|
but
s-r = -16+10 = -6
t-u = -15+10 = -5
This does not satisfy ( s-r > t-u ) so we cannot use the above logic.

------------------------------------------------------------------------------

Actually
|S-R| >= |S| - |R|
or
|S+R| <= |S| + |R|

Applying this logic to condition 1

(1)|R-T|>|S-U|

( |R-T| >= |R|-|T| ) > ( |S-U| >= |S|-|U| )

Let us assume that |R-T| > |R|-|T| and not greater than or equal to
then
|R|-|T| > |S|-|U| let us rearrange this equation
-|S|+|R| > |T|-|U|
so |S|-|R| < |T|-|U| this gives the answer to the question
but the problem is
|R-T| can be equal to |R|-|T| and |S-U| can be greater then |S|-|U| then
we cannot say for sure |R|-|T| > |S|-|U|
The same rule applies to condition 2, and for this reason alone we cannot combine the derivatives of conditions 1 and 2.
Thus we can conclude that neither of the conditions can be used to solve the inequality.

[/b]
Intern
Joined: 04 Oct 2003
Posts: 42
Location: Silicon Valley, CA
Followers: 0

Kudos [?]: 1 [0], given: 0

### Show Tags

20 Dec 2003, 21:58
Thanks Anand.
I tried to over simplify the problem.
Intern
Joined: 04 Oct 2003
Posts: 42
Location: Silicon Valley, CA
Followers: 0

Kudos [?]: 1 [0], given: 0

### Show Tags

21 Dec 2003, 14:38
Anand I see a problem with your objection.

putting the values that you chose

S - R > T- U => 6 > 5
S - R < U -T => -6 < 5 (sign of inequality reverses)

so the technique used by Racer seems to be correct.
Your explantion is elaborate and correct too. For GMAT we need short cut methods for problems.

Racer how did you solve the two (A. and B.) to get
S > R.
Could you please explain this.

Thanks.
SVP
Joined: 30 Oct 2003
Posts: 1790
Location: NewJersey USA
Followers: 6

Kudos [?]: 101 [0], given: 0

### Show Tags

21 Dec 2003, 16:32
I could not agree with you more. I am not sure I would have solved the question in two minutes. We definitely need shortcuts. I just feel that arriving at correct answer does not mean the method of solving the problem is correct. A slight twist in the question can make the solution invalid and can give you wrong answers.
I tried to put the solution because new comers can learn little bit about the absolute inequialities. I have learnt a lot from people like you by going through the post and I would like to contribute wherever I can.

Thanks,
Anand.
Intern
Joined: 04 Oct 2003
Posts: 42
Location: Silicon Valley, CA
Followers: 0

Kudos [?]: 1 [0], given: 0

### Show Tags

21 Dec 2003, 17:12
You are a good man Anand.

Hey, could any one verify IF this is correct.

say we have

a-b > c-d
a-b > d-c

so can we say

a-b> 0 => a>b.

Any takers for this....
Senior Manager
Joined: 11 Nov 2003
Posts: 357
Location: Illinois
Followers: 1

Kudos [?]: 5 [0], given: 0

### Show Tags

24 Dec 2003, 16:47
I think this problem should be approached in the following way. I know that the method looks very long but I think if understood once, it should not take long to do similar problems. In a way, it is just an extension of Racers approach.

We know that |x| = x, if x > 0 but |x| = -x if x < 0.

So any inquality |x| > |y| can result in the following possibilities:

x is +ve and y is +ve => x > y
x is -ve and y is -ve => -x > -y
x is +ve and y is -ve => x > -y
x is -ve and y is +ve => -x > y

Applying this logic, what we need to find here is Is |S-R|>|T-U|? In other words,

Is S-R > T-U? or
Is R-S > U-T? OR
Is S-R > U-T? OR
Is R-S > T-U? ========================(Q)

Now applying the logic to statement 1,

|R-T|>|S-U|, is this sufficient to say that ANY ONE of the above 4 possibilities is correct?

Let us see, this statement will give following possibilities

R-T > S-U => R-S > T-U (This is one of the possibilities in Q above. So the answer is YES)
T-R > U-S => S-R > U-T (So the answer is YES again)
R-T > U-S => R+S > T+U (Can not say )
T-R > S-U => T+U > S+R (Can not say)

Statement 1 NOT SUFF

Similarly statement 2 will give 4 possibilities, 2 of which will answer the question in YES and remaining 2 will not answer. So statement 2 NOT suff.

TOGETHER

Both the statments taken togethet will also result in the 4 possibilities that are mentioned in BOLD above.

So together NOT SUFF.

This will give answer E.

Can you guys comment on this method?

Akmai, can you also jump in here? Thanks
24 Dec 2003, 16:47
Display posts from previous: Sort by

# Is |S-R|>|T-U|? (1)|R-T|>|S-U| (2)|R-U|>|S-T|

 post reply Question banks Downloads My Bookmarks Reviews Important topics

 Powered by phpBB © phpBB Group and phpBB SEO Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.